Produksi Materi Promosi Instagram Reels dalam Meningkatkan Brand Awareness Vasaka Solterra - Indah Ratna Dewi; Amiruddin Saleh (Pusat Riset dan Inovasi Nasional, 2025)
The rapid growth of social media in Indonesia has transformed marketing communication strategies, particularly in producing creative promotional content. Instagram Reels has emerged as an effective platform for building brand awareness through short and engaging videos. This study was conducted during an internship at PT Waskita Fim Perkasa Realti and focuses on the production process of Instagram Reels content for Vasaka Solterra. The first objective is to examine the workflow of promotional video production across three stages, pre-production, production, and post-production. The second objective is to identify challenges faced by the Marketing Communication Division. Using qualitative methods, including observation, interviews, participation, and literature review. This study found that pre-production involves idea development, content research, and storyboard creation. The production stage includes smartphone-based video shooting and voice-over recording to ensure message clarity. Post-production centers on editing using CapCut and applying a consistent visual identity before publication. The study also identifies several obstacles, such as limited human resources, minimal equipment availability, and coordination delays with external partners. These findings highlight the need for increased production personnel, improved interdepartmental collaboration, and enhanced equipment support to optimize the overall content production process.